Low-wage employment versus unemployment: Which one provides better prospects for women? - Alexander Mosthaf; Thorsten Schank; Claus Schnabel (IZA Journal of European Labor Studies, 2014)
Using German SOEP data, 1999 - 2009, this study analyzes state dependence in low-wage employment of western German women, where we distinguish between full-time and part-time working. We estimate a dynamic multinomial logit model with random effects and find that having a low-wage job - compared to having a high-wage job - ceteris paribus decreases the probability of being high-paid in the future. This negative effect is significantly larger for part-time jobs than for full-time jobs. We find mixed evidence for a low-pay-no-pay cycle: compared to being high-paid, having a low-paid job increases the risk of being unemployed in the next period only for part-time workers. However, concerning future wage prospects low-paid women are clearly better off than unemployed or inactive women. We argue that for women low-wage jobs can serve as stepping stones out of unemployment and are to be preferred to staying unemployed and waiting for a better job.
Keywords: J30; J60; C35; 330; Low-pay dynamics; State dependence; Dynamic multinomial logit model